Enhanced Dentinogenesis of Pulp Progenitors by Early Exposure to FGF2. (November 2015) - Sagomonyants, K.; Kalajzic, I.; Maye, P.; Mina, M.
Members of the fibroblast growth factor (FGF) family play essential and important roles in primary and reparative dentinogenesis. Although there appears to be a general agreement on the effects of FGF signaling on the proliferation of pulp cells, there are conflicting results regarding its effects on odontoblast differentiation. We recently examined the effects of continuous exposure of dental pulp cells to FGF2 and showed that the effects of FGF2 on differentiation of progenitor cells into odontoblasts were stage specific and dependent on the stage of cell maturity. The purpose of this study was to gain further insight into cellular and molecular mechanisms regulating the stimulatory effects of FGF2 on odontoblast differentiation. To do so, we examined the effects of early and limited exposure of pulp cells from a series of green fluorescent protein (GFP) reporter transgenic mice that display stage-specific activation of transgenes during odontoblast differentiation to FGF2. Our results showed that early and limited exposure of pulp cells to FGF2 did not have significant effects on the extent of mineralization but induced significant increases in the expression of Dmp1 and Dspp and the number of DMP1-GFP + and DSPP-Cerulean + odontoblasts. Our results also showed that the stimulatory effects of FGF2 on odontoblast differentiation were mediated through FGFR/MEK/Erk1/2 signaling, increases in Bmp2, and activation of the BMP/BMPR signaling pathway. These observations show that early and limited exposure of pulp cells to FGF2 alone promotes odontoblast differentiation and provides critical insight for applications of FGF2 in dentin regeneration.